The value of evaluation making training evaluations more effective - Wentworth, David (IG library, 2009)
Measuring the impact of learning continues to be one of the most challenging aspects of the learning function. ASTDs Value of Evaluation report explores the complex issue of learning evaluation, the techniques being used, barriers to effective implementation, and strategic use of learning metrics. Companies employ myriad strategies to identify and quantify the results of training, but most are not satisfied with the evaluation efforts. Organizations are not giving up on successful measurement of the learning function, as they continue to explore ways to communicate and document the value of training and development they provide to employees. The data in this report can help many firms become more proficient in these areas.